Algoritma Penentuan Ukuran Batch Integer pada Penjadwalan Flowshop Satu Mesin - Hadigufri Triha; Ahmad Syafruddin Indrapriyatna; Jonrinaldi Jonrinaldi; Berry Yuliandra (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
Scheduling is an important area of production planning and control. Scheduling is required to produce an existing job by allocating existing resources in the proper execution order. Production schedules arranged effectively and efficiently to maximize resources utility, minimize waiting and idle time and increase productivity. The flowshop batch scheduling model for one machine that takes inventory and quality cost into account has been developed by Indrapriyatna et al (2007a). However, the model yet effective in converting the results of batch size into integers. This study tried to resolve this problem by using a modification of Branch and Bound Algorithm approach.